Cloud computing and 5G challenges and open issues - Arif Ullah; Hanane Aznaoui; Canan Batur Şahin; Mahnaz Sadie; Ozlem Batur Dinler; Laassar Imane (International Journal of Advances in Applied Sciences, 2022)
The obtainable fourth-generation technology (4G) networks have been extensively used in the cloud application and are constantly evolving to match the needs of the future cloud applications. The ﬁfth-generation (5G) networks are probable to immense expand today's cloud that can boost communication operations, cloud security, and network challenges and drive the cloud future to the edge and internet of things (IoT) applications. The existing cloud solutions are facing a number of challenges such as large number of connection of nodes, security, and new standards. This paper reviews the current research state-of-the-art of 5G cloud, key-enabling technologies, and current research trends and challenges in 5G along with cloud application.